Developing inter-collegial friendships to sustain professional wellbeing in the academy. Issue 3 (18th May 2020) - Garbett, Dawn; Thomas, Lynn
ABSTRACT: In this self-study, we explore the benefits associated with developing inter-collegial friendships for sustaining our wellbeing in the academy. We have used anticipatory reflection to imagine what our idealised working situation might look like and then taken measured steps towards supporting one another to achieve our goals. Our research focus - to question how collaborative, professional friendships can help us achieve professional satisfaction and sustain us in times of personal and professional flux – has given rise to new understandings about ourselves. These new understandings include firstly, how taking care of ourselves physically has made us aware of our embodied knowing about the roles we take in the academy. Secondly, we describe the importance of showing appreciation and being affirmed by others to counter the culture of constant evaluation. Thirdly, we have negotiated a more horizontal relationship with our institutions, cognisant of the parameters prescribed by our roles and circumstances. We are learning to care about ourselves so that we can offer our best to our students, our institutions and to our families and friends. We share our findings here in the hope that they may help other academics achieve wellbeing in the workplace.